Good citizens: legitimization strategies of new religious movements in Israel - Ben-Porat, Gay (Politics and religion, 2025)
The presence of new religious movements (NRMs) is often fraught with tensions and confrontations. Depicted as foreign elements and "cults" they face opposition demanding to restrict their activities. NRMs in Israel, despite small numbers, raised concerns and objections, attributed among other things to the dominance and power of Orthodox religion. Gradually, however NRMs managed to establish themselves in Israel and to successfully deflect the opposition to their presence. In this work, based on interviews and media reports, we explore two strategies that enabled the movements in Israel to minimize rejection and opposition to their presence. The first, based on a republican concept of citizenship, included the adoption of Zionist ideology and taking part in settlement ethos and military service. The second, based on neoliberal concept of citizenship, fits well with more current trends in Israel, offers paths to economic advancement and social mobilization through education and ethos of success.